Pengelolaan Usaha Pada Usaha Mikro Kecil Menengah Dengan Strategi Pemasaran Pada UMKM “X” Di Kelurahan Jember Lor - Endang Lifchatullaillah; Nely Supeni; Indra Legiyanti (STIKes Ibnu Sina Ajibarang, 2023)
Community Service is a lecturer's obligation which must be carried out as an implementation and recognition of the Tridharma of Higher Education, and is a lecturer's concern for environmental sustainability and the existence of community life. One form of concern from researchers which focuses on the community economic sector is still being carried out in order to play a role in the development of the nation's economy. The methodological approach used by researchers is to provide counseling and assistance to micro, small and medium business actors in managing their businesses with marketing strategies to increase profitability in their businesses. Micro, Small and Medium Enterprises (MSMEs) are one of the economic implementers that give color to Indonesia. The number of MSMEs is increasing every year and has absorbed a lot of workers. The existence of MSMEs is part of human life activities to meet their daily needs as well as their existence in the era of economic globalization and the ability to survive in the face of the economic crisis and during the Covid-19 pandemic. Marketing also requires a strategy that will later be able to win a battle. Because he considers that there are many opponents in the market field who have similarities in their business and should not be turned off. As in the Pancasila economic system, fellow market players should have a sense of mutual care from large entrepreneurs towards smaller entrepreneurs. Therefore, it is necessary to have a Grand Strategy and a Core Strategy or what is called a Core Strategy. (Buchari, 2018) Almost every month MSMEs in the Jember Lor area continue to increase, more people choose business as a way to gain financial income for the family. However, MSME business is still carried out conventionally without any thought for the development of the business. As explained above, assistance is needed for MSME business actors who are willing to become respondents to gain knowledge about marketing strategies in order to increase profits and ensure that their business can survive and develop.